IMPROVING THE MECHANISM OF DEVELOPING INNOVATIVE COMPETENCE OF FUTURE TEACHERS IN THE PROCESS OF INDEPENDENT LEARNING - Tangirbergenova Mexriban Ko'shkinbaevna (Modern American Journals, 2025)
This article comprehensively covers the issues of developing innovative competence of future teachers in the process of independent learning. In the context of modernization of the educational process, a teacher is required not only to possess theoretical knowledge, but also to form the ability to perceive innovations, analyze them and effectively apply them in practice. From this perspective, the concept of innovative competence and its components are analyzed, and the importance of this competence in preparing future teachers for professional activity is revealed. The article substantiates the specific features of independent learning, its role in developing creative thinking in students, using digital technologies and strengthening the ability to find new solutions to problems. It also shows the effectiveness of using project-based assignments, research activities, reflection and self-assessment methods in organizing independent learning.
Keywords: Independent learning, innovative competence, future teacher, pedagogical technology, creative approach, information and communication technologies.